2017
DOI: 10.1016/j.addma.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Functionally graded Ti6Al4V-Mo alloy manufactured with DED-CLAD® process

Abstract: This paper presents the results of functionally graded Ti6Al4V-Mo alloy manufactured with directed energy deposition called CLAD ® (Construction Laser Additive Direct) process. Single track width sample with five gradients of composition, from 0 to 100 wt.% Mo, was manufactured using a coaxial nozzle. Both Ti6Al4V and Mo ratios were modified with a 25 wt.% increase or decrease in the chemical composition of each gradient. A two-powder feeder was used to input the correct ratio of each powder, so as to obtain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…The microstructure features of the different graded materials in their as-deposited states has been detailed previously [34,35]. The main features are just recalled in Figure 1b,c for the sake of clarity.…”
Section: Evolution Of the Microstructure Along The Gradientmentioning
confidence: 99%
See 3 more Smart Citations
“…The microstructure features of the different graded materials in their as-deposited states has been detailed previously [34,35]. The main features are just recalled in Figure 1b,c for the sake of clarity.…”
Section: Evolution Of the Microstructure Along The Gradientmentioning
confidence: 99%
“…The powders and manufacturing data (power, speed, pitch, etc.) of the samples have been detailed in the works of Schneider et al [34,35]. The FGM walls were cut into 1.5 mm thick slices.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…T good miscibility between the two materials), and sharp interfaces which form intermetallic phases, that have bad mechanical properties and tend to separate easily. For example Schneider-Maunoury et al [6] showed that there is a good metallurgical bonding between different gradients in a Ti6Al4V-Mo alloy FGM made with CLAD®. Moreover Onuike and Bandyopadhyay [7] studied the interface between Inconel 718 and Ti6Al4V using additive manufacturing and showed that to construct a FGM with these two materials, a buffer material is needed due to numerous defects (delamination, intermetallic phases, cracking) when the two materials are directly in contact.…”
Section: Introductionmentioning
confidence: 99%